“THE ROLE OF SHAKESPEARE IN THE DEVELOPMENT OF ENGLISH LITERATURE” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the outstanding role of William Shakespeare in the development of English literature. It analyzes his contribution to the enrichment of the English language, dramatic art, and literary thought. The study highlights how Shakespeare’s creativity, linguistic innovation, and philosophical depth transformed literature from the Renaissance to the modern era. His works not only shaped poetic and dramatic forms but also influenced global culture, education, and artistic expression. The findings show that Shakespeare remains a timeless figure whose language, characters, and universal themes continue to inspire readers and writers worldwide.